Komitet do Spraw Szlachty Zagrodowej na Wschodzie Polski 1938-1939 - Kacprzak, Michał (Acta Universitatis Lodziensis. Folia Historica, 2005)
One of the results of long standing annexations was liquidation of the whole social stratum which nobility had presented before partitions. The first actions to make the descendants of the former nobility become the Poles took place in 1934. In north-eastern terrains the actions took place later and in a different way. The action of the recapturing of nobility was begun in turczański administrative unit, and it was spread on the eastern province in southern Poland and Wołyń. The noble youth were led to special military units. A periodical tilled ‘Wake up’ was started to distribute to backwaters. The organizing of the circles of nobility, common rooms, cooperatives, agricultural was started as well. The Secretariat of Polish Social Organizations was responsible for the coordination of the actions. On behalf of Polish Social Organizations the action was taken by the Company of the Development of Eastern Lands. But with time the problem became so much momentous that in November 1937, during the special conference organized by Ministry of Military Affairs, representatives of ministries, institutions and army decided to appoint interministerial Nobility’s Affairs Committee. But instead of it on 25th February 1938 Nobility’s Affairs Committee was appointed within the Company of the Development of Eastern Lands. The activity of the committee was run in lour sections: scientific, propaganda, economic and financial. The committee was patronizing to the actions of Nobility Union which numbered about six hundred and thirty of circles and fifty thousand of members in 1939. The scientific section fulfilled a crucial role in the workings of the committee. Work was due to be run as a national activity, not political and adjusted to the local conditions and coordinated with the whole of Polish work in the East.